Asthma In Children: Principles Of Diagnosis And Management (The Review of Diabetic Studies, 2025)
Background: Asthma is a persistent affliction that affects nearly 262 million people and is the most common chronic illness in children. Given the sensitive nature of the pediatric population and the long-term side effects that might be associated with the various treatment modalities available for treating asthma, it is essential to review the latest therapies and guidelines to provide the best possible care to the children.Objective: To objectively review the latest methodology for diagnosis and management of asthma in the pediatric population.Materials and methods: This review is a comprehensive search of PUBMED from the year 2005 to 2025.Conclusion: Pediatric asthma is a complex condition that requires the involvement of the patients, caregivers, and the healthcare team to administer medication and prevent any morbidities and mortality in the young patients involved. A comprehensive treatment plan with minimal adverse effects and future repercussions for the child should be considered, which should be revised regularly depending on the response to the therapy.